Circulating blood biomarkers in essential hypertension: a literature review - Shere, Amar; Eletta, Olanrewaju; Goyal, Hemant (Journal of Laboratory and Precision Medicine, 2017)
Hypertension is a global public health issue, affecting over 70 million Americans and about one billion people worldwide. Hypertension is a significant public health concern as it is a major risk factor for stroke, coronary artery disease (CAD), renal disease, heart failure, and peripheral vascular disease. Nearly two-thirds of hypertensive persons are unaware of their condition, and therefore, are not being treated to prevent the development of complications. Approximately 90% of hypertensive patients suffer from primary or essential hypertension (EH), a term which is used when the cause of blood pressure (BP) elevation is unknown. With any chronic condition that leads to devastating consequences, early diagnosis and timely interventions are crucial. This strategy proves to be true for EH as well, as it can decelerate disease progression, reduce complications and ultimately produce better outcomes. Over the years, various blood biomarkers have been identified which can shed light on the underlying processes involved in the onset, development, and progression of EH. As data from the Framingham Heart Study indicate that about 90% of people over the age of 55 will eventually develop hypertension, discovering and utilizing reliable biomarkers to predict, diagnose, and track the therapeutic progress of hypertension is proving to be tremendously important. Here, we provide a literature review of circulating biomarkers that may prove to be beneficial in better elucidating the pathophysiology, development, progression, and therapeutic efficacy of EH.